A contribution for qualitatively modeling of friction and wear behavior of thermoplastics - Drummer, Dietmar; Kobes, Michael; Merken, Daniel (SPE Proceedings ANTEC 2012, 2012)
Tribological parameters are results of a complex system; therefore their behavior can not easily be predicted. This paper suggests a model for characterizing tribological behavior by the distinct contribution of basic friction, and wear modes. These modes and the transition from one to another are influenced by material, geometric, and other system properties. The presented model is based on broadly accepted, mostly two-dimensional, correlations and supported with own pin-on disc friction and wear experiments.
UnivIS-Import:2015-04-16:Pub.2012.tech.FT.FT-KT.acontr